Determinants of stunting in Samadua sub-district, South Aceh district - Rossi Aulia Pratiwi; Ikeu Ekayanti; Eny Palupi (AcTion: Aceh Nutrition Journal, 2024)
Stunting remains a major malnutrition problem in Indonesia, and is caused by chronic malnutrition and recurrent infections. In 2022, the SSGI reported that Aceh ranked fifth with a high prevalence of stunting (>30%). Malnutrition during the golden period (toddlers) can be corrected. This study analyzed the factors that influence stunting and the most dominant factors in children aged 6-24 months in the Samadua District, South Aceh Regency. This study was conducted using a cross-sectional design. Participants were 120 children under five years of age conducted in Samadua District by simple random sampling from November 2023 to January 2024. Data were collected through interviews, using questionnaires, anthropometric measurements, and recall. Statistical applications were used for data processing. Bivariate data analysis was performed using binary logistic regression test with p<0,25 criteria and multivariate analysis was continued using logistic regression test on influential variables in bivariate analysis and 95% confidence interval (CI). Conclusion: Risk factors affecting stunting in children aged 6-24 months in Samadua District, South Aceh Regency, were birth length (OR=13,000), birth weight (OR=15,400), maternal anemia history (OR=18, 000), ANC history (OR=20,429), ARI frequency (OR=7,500), protein adequacy (OR=5,910), fat  (OR = 7,083), calcium (OR = 6,081), iron (OR = 4,375), and zinc (OR = 5,500) intakes.